Experimental study on the mechanical behavior of concrete incorporating fly ash and marble powder waste - Abdul Ghani; Fasih Ahmed Khan; Sajjad Wali Khan; Inzimam Ul Haq; Dongming Li; Diyar Khan; Qadir Bux alias Imran Latif Qureshi (Scientific Reports)
Abstract This research is focused on the development of an eco-friendly low-cost concrete using fly ash (FA) and marble powder waste (MPW) as partial replacements for cement and fine aggregate respectively. The substantial use of cement in concrete makes it expensive and contributes to global warming due to high carbon emissions. Thus, using such waste materials can help reduce the overall carbon footprint. For this purpose, various mix designs of concrete were developed by varying the percentages of FA and MPW. The concrete's fresh and hardened properties were experimentally determined for those mixes. The test results revealed that MPW as a sand substitute increases strength up to 40% and gradually decreases beyond that, but a 60% replacement still has more strength than the control specimen. Similarly, using FA as a cement replacement was found to reduce the strength, but the reduction was not very significant up to 20%. A mixed blend of FA and MPW showed superior results and maximum strength was obtained at F10M40. The optimal mix, with 10% FA and 40% MPW (F10M40), achieved a compressive strength of 4493.46 psi, a 16.21% improvement compared to the control mix proportion. Furthermore, the microstructure of the cementitious material was improved due to the pozzolanic reaction that led to a denser microstructure, as supported by the permeability test and SEM analysis.